David Hare bicentenary volume, 1975-76 - Hare, David, 1775-1842; Bhattacharya, Rakhal, 1910- (David Hare Bicentenary of Birth Celebration Committee : selling agents, Firma KLM, 1976)
On the life and contributions of the Scottish educationalist and philanthropist, David Hare, 1775-1842, to educational reform in 19th century Bengal; contributed articles.